Estrogen receptor-ID4 cross talk in breast cancer - Nasif, Daniela Lucía (2020)
Inhibitor of differentiation (ID) 4, a member of the ID family, has been shown to act as a tumor suppressor and as an oncogene in breast cancer. Our group has investigated this apparent discordant information and has found evidence that ID4 acts as a tumor suppressor only in estrogen receptor ER+ tumors and as an oncogene only in ER- tumors. Here we focus on ID4?s tumor suppressor role and further investigate why ID4 is aberrantly methylated exclusively in ER+ tumors.EZH2 is a histone methyltransferase involved in the tri-methylation of lysine 27 on histone 3 (H3K27me3) and also promotes DNA methylation via DNMT recruitment. In breast cancer EZH2 is overexpressed and downregulates the expression of tumor suppressor genes via increased promoter H3K27me3. Since ID4 is hyper-methylated in ER+ tumors and since EZH2 expression is induced by estradiol we hypothesize that estradiol induces ID4 methylation through EZH2. We performed siRNA (EZH2), immunofluorescence and chromatin immunoprecipitation (CHIP) experiments in MCF7 breast cancer cell lines. Our results show that EZH2 regulates ID4 expression as confirmed by siRNA experiments, that estrogen treatment increases EZH2 expression and ID4 methylation and CHIP experiments reveal that estrogen administration increases EZH2 and H3K27me3 marks on ID4 promoter. Taken together our results show for the first time that estradiol induces ID4 methylation trough EZH2 in breast cancer cell lines.